2017
DOI: 10.33549/physiolres.933586
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Carp Meat From Two Aquaculture Production Systems Aimed at Secondary Prevention of Ischemic Heart Disease – a Follow-up Study

Abstract: Our previous study showed that a diet enriched with 400 g of carp per week improved plasma lipids in subjects after aortocoronary bypass (CABG). The aim of the present study is to determine whether the different carp farming systems have an impact on the effects of carp meat in secondary cardiovascular prevention. We examined 3 groups of patients after CABG over a 4-week period of spa treatment (108 persons, 73 males, 35 females, age over 60 years). We found no differences in baseline values of blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…As a result, n‐3/n‐6 ratio of OCC was 5.6 times higher than that of NCC. The information of fatty acids and lipid content of OCC was consistent with that reported by Mraz et al ., 8 indicating that OCC had lower lipid content along with an improved fatty acid profile featured with higher content of n‐3 PUFA, EPA + DHA, n‐3/n‐6 ratio compared with NCC. The beneficial effects of n‐3 PUFAs on human mental and bone health, as well as in the control and treatment of different diseases such as heart disease, diabetes, arthritis, cancer and obesity have been extensively reported 1,24 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As a result, n‐3/n‐6 ratio of OCC was 5.6 times higher than that of NCC. The information of fatty acids and lipid content of OCC was consistent with that reported by Mraz et al ., 8 indicating that OCC had lower lipid content along with an improved fatty acid profile featured with higher content of n‐3 PUFA, EPA + DHA, n‐3/n‐6 ratio compared with NCC. The beneficial effects of n‐3 PUFAs on human mental and bone health, as well as in the control and treatment of different diseases such as heart disease, diabetes, arthritis, cancer and obesity have been extensively reported 1,24 .…”
Section: Resultssupporting
confidence: 89%
“…Common carps produced by this system showed higher level of n‐3 fatty acids and n‐3/n‐6 ratio than normal common carps (NCCs) from traditional semi‐intensive culture system. Studies showed that these OCC had positive effects on alleviating ischemic heart disease symptoms 8,9 . The high healthy and economic value are driving more aquaculture companies to adopt this system for producing OCC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, fish is rich in protein, fat‐soluble vitamins, minerals, omega‐3 fatty acids (ω−3 FAs), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA). It benefits human cardiovascular and cognitive (neural) health (Abedi & Sahari, 2014; Linhartová et al., 2018; Mraz et al., 2017; Tilami & Sampels, 2018). Simultaneously, fish meat is highly perishable (i.e., susceptible to “rapid” decline in quality) because of high water content, the potential for protein degradation, lipid oxidation, and other reactions caused by bacterial and enzymes action.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater and marine fishes play a significant role in human nutrition as a source of protein and other nutrients (FAO 2016). They provide crucial elements of a healthy diet including digestibility, low fat content, essential vitamins and minerals, and a higher content of unsaturated fatty acids compared to terrestrial animal fat (Adamkova et al 2011;Lund 2013;Mraz et al 2017;Linhartova et al 2018). The nutritional composition of fish muscle is influenced by many factors such as fish species, age, gender, rearing conditions, breeding technology, and season, etc.…”
Section: Introductionmentioning
confidence: 99%